Flexible Piezoelectric Fibers for Acoustic Sensing and Positioning - Wang, Shun (2017)
Emerging development of flexible acoustic devices focuses on constructing large-area acoustic sensing networks with high spatial and temporal resolution, enabling applications in acoustic sensing and positioning, particularly in underwater and medical fields. Here, a piezoelectric fiber-like device is fabricated by a thermal drawing technique to deliver acoustic sensing functionalities at fiber-optic length scales, flexibility, and uniformity. The resulting piezoelectric fiber device operates in a frequency range of 2–8 MHz with signal-to-noise ratio above 20 dB. Additionally, a single piezoelectric fiber can simultaneously demodulate two monochromatic sound signals with a frequency gap from 0.01 to 30 MHz. As a proof of concept, a 2D 3 × 3 fiber array is fabricated to detect and position an underwater acoustic source with a spatial resolution of one centimeter.